Comparison of finishing and polishing systems for residual resin removal after debonding (Journal of Applied Oral Science, 2009)
OBJECTIVE : The aim of this study was to evaluate (1) the effectiveness of one-step polishers on the surface morphology of enamel using scanning electron microscope (SEM) and compare their effects with conventional systems for residual adhesive removal; and (2) the time spent to remove resin remnants. MATERIAL AND METHODS: Metal brackets were bonded to the buccal surface of 80 freshly extracted human premolar teeth and received the same resin-removal methods to evaluate the time spent to remove resin remnants (n=10). The brackets were debonded and residual adhesive was removed using different systems. Fourty-five premolars, including the control group with intact enamel (n=5), were examined by SEM. RESULTS: 30-blade tungsten carbide burs were the least time-consuming procedure. The best system in SEM study was the PoGo micro-polishers followed by Super-Snap Rainbow system. CONCLUSIONS: The effect of polishing systems on residual resin removal was dependent on the characteristics of the instruments in each system.